Changes in lamotrigine pharmacokinetics during pregnancy and the puerperium - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
To assess changes in the pharmacokinetics of the antiepileptic drug lamotrigine (LTG) during pregnancy, plasma LTG concentrations at steady-state were determined at different intervals during 11 pregnancies in 10 women with epilepsy stabilized on long-term LTG therapy. In the five pregnancies that could be assessed both during gestation and after delivery, plasma LTG concentrations increased on average by 164% (range +75 to +351%) between the last observation during pregnancy and the puerperium (P < 0.05). When all pregnancies monitored during pregnancy were considered, plasma LTG concentrations declined by an average of 20% (range -64% to +13%) between the first and the last assessment before delivery. These findings confirm that plasma LTG concentrations decrease markedly during pregnancy and that, at least in some cases, this effect occurs as early as the first trimester. Because there is a large interindividual variability in the magnitude and time course of the pregnancy-associated pharmacokinetic changes, it is desirable to establish baseline plasma LTG concentrations in all women of childbearing potential and to monitor LTG levels at frequent intervals during pregnancy and the puerperium.
Keywords: lamotrigine; pharmacokinetics; pregnancy; epilepsy; therapeutic drug monitoring; ANTIEPILEPTIC DRUGS; PROTEIN-BINDING; DISPOSITION; VALPROATE; PLASMA; ANTICONVULSANTS; OXCARBAZEPINE; METABOLISM; CLEARANCE; EPILEPSY